A teoria da prova segundo o constructivismo lógico- semântico aplicada ao direito previdenciário - Vieira, Ester Moreno de Miranda (2011)
This study aims to analyze the theory of evidence that is defined by the logical-semantics constructivism applied to the pension right. Though the several conceptions of the proof word, by a methodological cut, coming from the proof concept as a legal fact in a large sense once established, this legal fact itself in its strict sense has the skills to establish or deconstruct a legal relationship of social security protection through the impact of the law rules. This ability to develop the law effects depends on the legal incidence of the laws, which the logical-semantics Constructivism, opposing to the traditional and worldwide theory of law, does not happen automatically, it depends on the work of a human being, which leads to the promotion of the movement of the standard structures. Analyzed the theory of proof from the perspective of the logical-semantics Constructivism, work combines efforts to demonstrate its applicability under the Social Security Law research field referring to the law protection status. The work inability is identified as the Social Risk and material aspect of such protection standard. Among the specific goals, the leading study seeks to brighten the concept of the "beginning of physical evidence" and analyzes the legitimacy of the so-called taxed evidence according to the General Social Security System